Em guarda - ed. Business Publishers International Corporation (Business Publishers International Corporation)
Existências: A. 1, nº4 A. 1, nº5 A. 1, nº8 A. 1, nº10 A. 1, nº11 A. 2, nº8 A. 2, nº12 A. 3, nº2 A. 3, nº3 A. 3, nº4 A. 3, nº7 A. 3, nº8 A. 3, nº9 A. 3, nº10 A. 3, nº11 A. 4, nº1 A. 4, nº7